Tips and tricks in Multislice CT coronary angiography - Cademartiri, F.; Palumbo, A.; Maffei, et al., E. (Acta Biomedica Atenei Parmensis, 2008)
The introduction of the multislice computed tomography (MSCT) scanners and their application to coronary imaging has created a new clinical imaging field. Even though MSCT coronary angiography has been reported to be able to detect significant stenoses with very high diagnostic accuracy, the clinical implementation is still difficult and the users are having difficulties in reproducing the results in literature, partly due to the limited experience in the field of coronary MSCT. Several details can be overlooked so that diagnostic mistakes are possible. In this paper we tried to collect a series of technical “tips and tricks” that might improve the quality of coronary imaging in the clinical practice.